Antioxidant activity and antimicrobial properties of Entada leptostachya and Prosopis juliflora extracts - Mercy C. Ruto; Christine M. Ngugi; Patrick G. Kareru; Kipyegon Cheruiyot; Sylvester O. Rechab; Edwin S. Madivoli; Jackson K. Mutembei; Pius K. Kairigo; Ernest G. Maina (AOSIS, 2018)
Background: Natural phytoconstituents produced by plants for their sustenance have been reported to reduce disease. Objectives: This study determined the phytoconstituents, antioxidant and antimicrobial activity of crude methanolic extracts of Entada leptostachya and Prosopis juliflora extracts. Methodology: Antioxidant activity was determined using 2,2-diphenyl-1-picrylhydrazyl and β-carotene assays; the total phenolic and flavonoid were estimated using Folin-Ciocalteau and aluminium chloride, whereas antimicrobial activity was determined using the zone of inhibition method. Results: Screening of the extracts revealed the presence of terpenoids, flavonoids, saponins and phenols. Fourier transform infrared spectra of the extracts revealed presence of hydrogen bonded -OH functional group. E. leptostachya barks had the highest antioxidant activity followed by P. juliflora roots, E. leptostachya roots and P. juliflora leaves [μg/mL]. Prosopis juliflora (roots) had the highest bleaching effect, whereas E. leptostachya (barks) had the lowest bleaching effect. The total flavonoids were determined to be 0.15 ± 0.02 mg/g, 1.18 ± 0.18 mg/g, 0.39 ± 0.05 mg/g and 0.64 ± 0.03 mg/g for E. leptostachya roots, E. leptostachya barks, P. juliflora leaves and P. juliflora roots extracts, respectively. The total phenols were determined to be 0.93 ± 0.18 mg/g, 2.69 ± 0.41 mg/g, 0.62 ± 0.08 mg/g and 0.62 ± 0.08 mg/g for E. leptostachya roots, E. leptostachya barks, P. juliflora roots and P. juliflora leaves extracts. All plant extracts exhibited moderate activity against the growth of selected microorganisms. Conclusion: Antimicrobial and antioxidant activity of the two plants was as a result of secondary metabolites found in the crude extracts.